"Dominance by birthright"? Reconfiguration of firm boundaries to acquire new resources and capabilities. Issue 9 (21st October 2019) - Chan, Jin Hooi; Reiner, David
Abstract : Purpose: The purpose of this paper is to examine pre-entry resources and capabilities (R&Cs) of de alio and de novo entrants in an emerging industry. Then, the authors investigate how entrants modify their firm boundaries, after entering a new industry, to acquire the R&Cs deemed critical to be competitive and survive in the industry. Design/methodology/approach: The analysis uses the global biofuel industry as a case study. The authors use multiple sets of data, including primary data collected from semi-structured interviews with industry stakeholders and experts across major biofuel-producing countries as well as quantitative data from industry reports. Findings: Firms typically deploy two successive strategies in order to survive and grow. First, they extend vertical boundaries to capitalize on their own pre-entry R&Cs. Then they move quickly to acquire new R&Cs, which are classified as critical in the value chain of the industry. A new taxonomy of pre-entry R&Cs is proposed to distinguish critical and non-critical forms of R&Cs, and to reflect the ease of acquisition of any requisite R&Cs, which are context specific. These strategic moves lead to the bi-directional vertical integration observed in the biofuel industry. Research limitations/implications: Managers need to be able to assess the opportunities for entry and subsequent strategies to be competitive by assessing their R&Cs in terms of criticality and ease of acquisition in their entry decision making. Originality/value: A new taxonomy of R&Cs of the firm is proposed which has theoretical significance and practical implications for new entrants.